Ribosome Profiling and RNA Sequencing Reveal Genome-Wide Cellular Translation and Transcription Regulation Under Osmotic Stress in Lactobacillus rhamnosus ATCC 53103 - Fan, Xuejing; Bao, Tianyu; Yi, Huaxi; Zhang, Zongcai; Zhang, Kenan; Liu, Xin; Lin, Xue; Zhang, Zhen; Feng, Zhen (Frontiers in Microbiology, 2021)
Abstract To determine whether osmotic pressure affects the translation efficiency of Lactobacillus rhamnosus, the ribosome profiling assay was performed to analyze the changes in translation efficiency in L. rhamnosus ATCC 53103. Under osmotic stress, differentially expressed genes (DEGs) involved in fatty acid biosynthesis and metabolism, ribosome, and purine metabolism pathways were co-regulated with consistent expression direction at translation and transcription levels. DEGs involved in the biosynthesis of phenylalanine, tyrosine, and tryptophan, and the phosphotransferase system pathways also were co-regulated at translation and transcription levels, while they showed opposite expression direction at two levels. Moreover, DEGs involved in the two-component system, amino acid metabolism, and pyruvate metabolism pathways were only regulated at the transcription level. And DEGs involved in fructose and mannose metabolism were only regulated at the translation level. The translation efficiency of DEGs involved in the biosynthesis of amino acids was downregulated while in quorum sensing and PTS pathways was upregulated. In addition, the ribosome footprints accumulated in open reading frame regions resulted in impaired translation initiation and elongation under osmotic stress. In summary, L. rhamnosus ATCC 53103 could respond to osmotic stress by translation regulation and control the balance between survival and growth of cells by transcription and translation.